ADIKARMA USM SHOWCASES UNIQUENESS OF MALAYSIAN CULTURE IN THAILAND - MPRC, Pusat Media & Perhubungan Awam (USM, 2017)
USM, PENANG, 29 January 2017 The Adikarma Performing Arts Group from Universiti Sains Malaysia (USM) presented a unique cultural performance at the ASEAN Cultural Exchange 2017 Programme in conjunction with the Prince of Songkla University (PSU) Open Week at its Trang Campus from 2530 January 2017 and the Che Bilang Region Malay Festival in Satun, Thailand from 2829 January 2017.